2022
DOI: 10.3389/fpsyg.2021.777937
|View full text |Cite
|
Sign up to set email alerts
|

Self-Worth as a Mediator and Moderator Between Teacher-Student Relationships and Student Engagement in Rural Schools

Abstract: This study examined how self-worth of students mediated and moderated their perceived positive teacher-student relationships and student engagement among middle-school students from rural China. Eighth graders (N = 838) completed surveys measuring their perceived relationships with teachers, their self-worth, and engagement. Statistical analyses revealed significant correlations among all three variables, with the strongest being between teacher-student relationships and student engagement. The structural equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 81 publications
(146 reference statements)
0
5
0
Order By: Relevance
“…In Wentzel's study, perceived teacher support can facilitate students' willingness to cognitively and behaviorally engage in academic tasks, teacher support was positively related to students' interest in engaging in interactive classroom tasks (Wentzel, 1997). Another research found that teacher support may generate good teacher-student connections that can improve students' social interaction and intellectual skills within a classroom environment (Huang et al, 2022). Positive relationships between teachers and students can be a key source of supporting students' academic efforts and, motivating them to engage more in academic activities and learning tasks (Cooper, 2014).…”
Section: The Relationship Between Perceived Teacher Support and Learn...mentioning
confidence: 99%
“…In Wentzel's study, perceived teacher support can facilitate students' willingness to cognitively and behaviorally engage in academic tasks, teacher support was positively related to students' interest in engaging in interactive classroom tasks (Wentzel, 1997). Another research found that teacher support may generate good teacher-student connections that can improve students' social interaction and intellectual skills within a classroom environment (Huang et al, 2022). Positive relationships between teachers and students can be a key source of supporting students' academic efforts and, motivating them to engage more in academic activities and learning tasks (Cooper, 2014).…”
Section: The Relationship Between Perceived Teacher Support and Learn...mentioning
confidence: 99%
“…Engagement is not only highly motivated state, but also strongly affected by emotions, which are an inherent part of the human existence in any context ( Brackett et al, 2021 ). Thus, while examining intrinsic factors, researchers also have found emotional intelligence (EI) to be an important predictor of academic engagement (e.g., Sinclair et al, 2003 ; Mavroveli et al, 2009 ; Durlak et al, 2011 ; Huang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are also studies that supported the above findings such as Rama and Sarada (2017), Sahay (2020), Singh (2018), Srinivasan and Pugalenthi (2020) who also reported that teacher competence significantly predicted self-esteem. On the other hand, the findings revealed that self-esteem partially mediated the link between teacher competence and engagement such as, Gebresilase and Zhao (2023), Huang et al (2022), Li et al (2022), Chang et al (2022), Achmad et al (2023), Kim et al (2017), Liu et al (2023) whose findings revealed that self-esteem mediated the link between teacher competence and engagement. Since the findings are in line with the majority of researchers, it can be inferred that self-esteem partially mediated the link between teacher competence and engagement.…”
Section: Discussionmentioning
confidence: 96%
“…Self-esteem has been considered as the mediator of teacher engagement because teachers feel engaged when they exhibit a high level of selfesteem (Pathardikar et al, 2022). Researchers (Gebresilase & Zhao, 2023;Huang et al, 2022;Li et al, 2022;Pathardikar & Srivastava, 2022;Mai, 2016;Chang et al, 2022;Achmad et al, 2023;Kim et al, 2017;Liu et al, 2023) tried to use selfesteem to mediate the relationship between teacher competence and engagement in their investigations. However, conceptual and population gaps emerged from the above investigations.…”
Section: Teacher Competence Self-esteem and Engagementmentioning
confidence: 99%